Calculation Method and Application of Methane Life Cycle Emission Reduction in Coal Mine - Wang, Wenhui (International Journal of Natural Resources and Environmental Studies, 2026)
The second largest greenhouse gas, methane (CH4), is mainly emitted from the coal industry. In order to propose targeted emission reduction measures, it is urgent to establish a refined emission accounting method. Based on the whole life cycle theory and carbon emission characteristics of coal mines, the mining and mining mines are divided into four stages: geological exploration, coal mining, post-mining activities and abandoned mines. The “IPC-2019 Guidelines” and “GB/T 32151.11-2018” established a method for accounting methane emissions during the whole life cycle of Jingong coal mines. Taking the methane emission of Fangzhuang Coal Mine in Jiaozuo, Henan Province from 2010 to 2017 as an example, it is calculated that the methane emission of coal mining stage in the whole life cycle accounts for about 80%, which is consistent with the historical methane emission law of coal mines in China revealed by the evaluation results based on T3 method. The establishment of this method can provide a theoretical basis for proposing effective measures to reduce methane emission and greenhouse effect in coal mines.